POPYT NA KREDYT HANDLOWY - Zawadzka, Danuta (Wydział Prawa i Administracji UAM, 2006)
The paper focuses on trade credit issues. The aim of the study was to characterise the demand for delayed payments on the grounds of a trade credit facility. The economic models presented in the paper, called by the author traditional, are the basis on which contemporary researchers use to verify empirically the motives behind the wish to delay payments in commercial transactions. The author concentrates mainly on the work of Swartz, Eliehausen and Wolken, and Laffer. The model approach for optimal amount of trade credit, trade credit demand and its essence as a part of money supply are presented in the paper.
THE DEMAND FOR TRADE CREDIT